2005
DOI: 10.1016/j.physe.2005.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phase transitions of spin chiral nanotubes

Abstract: Recently many interesting magnetic nanostructures have been fabricated and much attention is arising on the rich magnetic properties that originate in the quantum effects eminent in the nanoscale world. One of the peculiar aspects of the quantum effects is the spin excitation gap. In the spin-1/2 low-dimensional systems, the spin gap often appears when the lattice dimerization or the frustration in the spin-spin interaction are introduced. In the present study, we investigate the ground-state property of the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The valence bond solid (VBS) ground states were revealed to appear in some different spin tube systems. For example, the quantum Monte Carlo simulation study [24] suggested that several different types of the VBS ground state occur in some chiral spin nanotubes without frustration. The recent non-linear σ model and DMRG approach [25] indicated some three-leg higher spin tubes exhibit several Haldane phases.…”
Section: Introductionmentioning
confidence: 99%
“…The valence bond solid (VBS) ground states were revealed to appear in some different spin tube systems. For example, the quantum Monte Carlo simulation study [24] suggested that several different types of the VBS ground state occur in some chiral spin nanotubes without frustration. The recent non-linear σ model and DMRG approach [25] indicated some three-leg higher spin tubes exhibit several Haldane phases.…”
Section: Introductionmentioning
confidence: 99%
“…Although the SOP parameter can detect the change associated with this phase crossing, however it does not perform so well when trying to locate the position of those critical points. To this end, another order parameter called twisted-order parameter (TOP) has been introduced for spin chains [30] and some ladders [31,32]. The TOP being non-local, it can be considered as a close relative of the SOP.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction.-Spin tubes constitute a special class of quasi-one-dimensional spin ladder systems characterized by periodic boundary conditions in the rung direction [1][2][3][4][5][6][7][8][9][10][11][12][13]. The magnetic compound ½ðCuCl 2 tachHÞ 3 ClCl 2 , for sample preparation, see [14], is a geometrically frustrated triangular spin tube, the frustration being related both to the triangular arrangement of its rungs and to the twisted geometry of the legs, compare Fig.…”
mentioning
confidence: 99%